XIX International Botanical Congress, Shenzhen: report of the Nomenclature Section, 17th to 21st July 2017 Special Issue - Heather L. Lindon (PhytoKeys, 2020)
The International Code of Nomenclature for algae, fungi, and plants is a set of voluntary rules that govern the naming of these organisms. These rules are changed via a process that begins with the community suggesting amendments to the current Code and culminates in a meeting at which all the proposed changes are discussed, debated and voted upon, held every six years in association with an International Botanical Congress. The most recent meeting, five days of discussions and decisions of the Nomenclature Section of the XIX International Botanical Congress, took place in Shenzhen, China in July 2017. The resulting Shenzhen Code was published in 2018. This is the official report of the proceedings of the meeting for the historical record, covering the debate and decisions taken. It conveys a true and lively picture of the event, retaining the flavour of goodwill and humour that permeated the Nomenclature Section of the Shenzhen Congress.